PVT and phase behaviour of petroleum reservoir fluids - Danesh, Ali (Elsevier, 1998)
Full text e-book available as part of the Elsevier ScienceDirect Earth and Planetary Sciences subject collection.
Keywords: Oil reservoir engineering.; Phase rule and equilibrium.; elektronické knihy; electronic books